DOI: 10.11606/t.25.2015.tde-22062015-093920
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia da eletroestimulação neuromuscular no tratamento da disfagia orofaríngea em idosos acometidos por acidente vascular encefálico

Abstract: AGRADECIMENTOSAgradeço a Deus, que permitiu esta grande conquista e a possibilidade de novas oportunidades.Ao meu pai, minha mãe, à Cíntia, Lucas, Laura, Daniel, Laís, Eduardo e toda minha família. Por darem suporte em todos os momentos de dificuldade e compartilhar das minhas alegrias.Ao meu noivo, Eduardo, pela paciência e apoio em todos os momentos.À Profa. Dra. Giédre Berretin-Felix, a quem admiro muito, que me permitiu adquirir grandes conhecimentos pelos seus ensinamentos. RESUMOVárias são as propostas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Table 2 shows that, regarding the "Feeding time" domain that had lowest average between domains (31.8%), which involves the questions "I take longer to eat than others" and "I take too much time to eat my meal" that can be justified by any changes resulting from concomitant aging with the consequences of stroke, such as reduced muscle strength, incoordination of chewing and swallowing, the presence of oral and pharyngeal stasis, penetrations and laryngeal aspirations. In addition, increased feeding time may be a necessary strategy to minimize such effects while feeding, Mituuti and Khaldoun Woisard and Verin found that the domain that most interfered the quality of life referred to the feeding duration (17,23) . Regarding the comparison between genders (Table 3), there was no significant difference in the average presented in the fields, indicating that men and women had similar scores.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 shows that, regarding the "Feeding time" domain that had lowest average between domains (31.8%), which involves the questions "I take longer to eat than others" and "I take too much time to eat my meal" that can be justified by any changes resulting from concomitant aging with the consequences of stroke, such as reduced muscle strength, incoordination of chewing and swallowing, the presence of oral and pharyngeal stasis, penetrations and laryngeal aspirations. In addition, increased feeding time may be a necessary strategy to minimize such effects while feeding, Mituuti and Khaldoun Woisard and Verin found that the domain that most interfered the quality of life referred to the feeding duration (17,23) . Regarding the comparison between genders (Table 3), there was no significant difference in the average presented in the fields, indicating that men and women had similar scores.…”
Section: Discussionmentioning
confidence: 99%